The Remnant : Light of Dawn - Book 3 - Chapman, Vannetta (Eugene, Oregon : Harvest House Publishers, 2017)
"Before Dawn, What Dangers Lurk in the Darkness? For nine months, ever since a devastating solar flare caused a complete failure of the electrical grid, Shelby Sparks and her diabetic son, Carter, have been living at the ranch of Shelbys ex-high school sweetheart, Max Berkman. Mostly insulated from the chaos surrounding them, Shelby and Max discover that the Texas government has fled the capitol and is barely maintaining control of the state. The governor needs volunteers to search for the new federal government, but no one knows exactly where it might be located--if it even still exists--or what perils await those brave enough to take on the mission. Compelled by Carters desperate need for insulin and their God-given sense of duty, Shelby and Max answer the governors call and set out on a treacherous 600-mile journey, where they will experience the terrifying effects of unrestrained anarchy. If they have the faith and fortitude necessary to reach their destination, what will they find when they get there? In this thrilling conclusion to the Remnant trilogy, America is left teetering between total collapse and the dawn of a new and vastly different reality"--
Keywords: Regression (Civilization) -- Fiction; Survival fiction; Christian fiction; Dystopian fiction; Thrillers (Fiction)